PENGEMBANGAN PENDAMPINGAN USAHA KERAJINAN TANGAN MENGANYAM MANIK DI PONTIANAK - Yuliana Langki; Nuraini Asriati; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to examine the development of assistance in the business of weaving beaded handicrafts in Pontianak. This research approach is Design Based Research with applied research type. Researchers became participants as trainers. The mentoring model used is CEFE. CEFE mentoring in this study was implemented in 3 meetings for training to members. The application of CEFE is more about formulating the implementation of mentoring from entrepreneurs in this case craftsmen as heads of business groups in providing training to 11 members. Each meeting has obstacles and evaluations that become material for overall reflection to be improved at the next meeting. The results of the research include the development of CEFE mentoring to develop a curriculum and indicators related to mentoring. The strategic formulation of activities includes determining production targets, making production targets a training target, conducting regular assistance and training as well as conducting digital marketing education for business actors. Constraints faced include the production process, namely human resources and the sales and marketing processes are not yet extensive due to the lack of mastery of using digital marketing. Solutions that have been and have been carried out in overcoming obstacles include conducting training with a smaller scope adjusted to existing costs and maximizing offline sales.